THE IMPACT OF MARKETING STRATEGIES TOWARDS THE PERFORMANCE OF MUSEUMS IN JAKARTA - Zainal Berlian (Business and Entrepreneurial Review, 2009)
Marketing activities in museum stores offer significant opportunities to evaluate distinct strategies and their related performance in a nonprofit setting. Whereas the museum store was originally intended to provide financial support for the institution with which it was associated, it now provides an educational or mission-related opportunity as well. This research identified variable of elaborate product orientation, customer orientation, competitor orientation and sales orientation toward social effectiveness and economic effectiveness. Total 18 museum in Jakarta was surveyed by researcher with interview technique to the museum management. The finding of this research, museum management should combining the variables of product orientation, customer orientation, competitor orientation and sales orientation in order to achieve social effectiveness and economic effectiveness